Les pratiques paysannes de gestion des pesticides sur le maïs et le coton dans le bassin cotonnier du Bénin - Soulé Akinhola Adechian; Mohamed Nasser Baco; Irénikatché Akponikpe; Ibrahim Imorou Toko; Janvier Egah; Kévin Affoukou (VertigO)
The increased use of chemical pesticides, coupled with the agricultural boom that is taking place in recent years, raises questions about the vulnerability of natural resources, especially water resources in cotton areas in Benin. The present study aimed to focus on the practices of the use of chemical agricultural pesticides in link with peasants scale and their comparison to the recommended standards. The data analyzed have been collected in the municipality of Gogounou with 150 producers all across 6 villages. We found that the active ingredients of pesticides most discharged into the cotton basin of Benin were glyphosate, atrazine, Flubendiamide, Spirotetramat and pyrethroids (emamectin, cyfluthrin, cypermethrin, betacyfluthrin). A small proportion of insecticides is marketed by the informal circuit (09%) in contrast to the majority (60%) of insecticides which comes from this circuit. Similarly, unauthorized pesticides come mostly from informal circuit (93.9% of herbicides and 21.5% of insecticides). The majority of producers (90.3%) uses an average of 3.4 bottles of Tihan per ha (0.34 liter per hectare) higher than the average recommended. Doses of pesticides used per hectare increase as the fields are close to water resources. The disrespected management of pesticides found in this area could be a threat to the conservation of biodiversity and the productivity of natural ecosystems, the health quality of fishery products and the health of producers and consumers. Given this situation, the challenge of the research is to determine the current level of contamination of the water resources and the one of the government would be the initiation of projects to raise awareness of producers on a more rigorous management of pesticides.